Core Cross-linked Star Polymers for Temperature/pH Controlled Delivery of 5-Fluorouracil - Elizabeth Sánchez-Bustos; José M. Cornejo-Bravo; Angel Licea-Claverie (Journal of Chemistry)
RAFT polymerization with cross-linking was used to prepare core cross-linked star polymers bearing temperature sensitive arms. The arms consisted of a diblock copolymer containing N-isopropylacrylamide (NIPAAm) and 4-methacryloyloxy benzoic acid (4MBA) in the temperature sensitive block and poly(hexyl acrylate) forming the second hydrophobic block, while ethyleneglycol dimethacrylate was used to form the core. The acid comonomer provides pH sensitivity to the arms and also increases the transition temperature of polyNIPAAm to values in the range of 40 to 46°C. Light scattering and atomic force microscopy studies suggest that loose core star polymers were obtained. The star polymers were loaded with 5-fluorouracil (5-FU), an anticancer agent, in values of up to 30 w/w%. In vitro release experiments were performed at different temperatures and pH values, as well as with heating and cooling temperature cycles. Faster drug release was obtained at 42°C or pH 6, compared to normal physiological conditions (37°C, pH 7.4). The drug carriers prepared acted as nanopumps changing the release kinetics of 5-FU when temperatures cycles were applied, in contrast with release rates at a constant temperature. The prepared core cross-linked star polymers represent advanced drug delivery vehicles optimized for 5-FU with potential application in cancer treatment.